Regional Government Strategy in Improving the Quality of Education in 3T Regions (Case study of SMAN 6 Batam, Air Raja, Kec. Galang, Batam City) - Roha Purnama Putri; Alfariq Ramadani (COMPETITIVE: Journal of Education, 2024)
Education has a significant impact on supporting the quality of human resources. However, education in Indonesia is underqualified and unequal, especially in the 3T region. Therefore, the research discusses the problems that are occurring in the 3T area and the solutions offered by the government. This article uses qualitative research methods to describe and analyze the phenomena that occur in SMAN 6 Batam. The researchers found problems that occur frequently in SMAN 6. Batam is a problem for educators, transportation, and educational facilities. The solution offered by creating a bachelor's education program in the 3T area. Through the policy offered, we can solve the problem of a shortage of educators' energy resources. This article is expected to help the government focus on the problems that are happening in the 3T area. In addition, as an enhancement of the public's insight into the problems and solutions that can be used.